The reindeer companies of southern Norway: Natural resources, husbandry, prerogatives and challenges (Article in Norwegian and in English) - Helland, Gaute Elvesæter; Stokstad, Jan (Rangifer, 2005)
From the middle of the 18th century there have been domesticated reindeer herds in the mountains of South-Norway. The people living in these areas, mostly farmers and hunters, bought reindeer from the Sami further east and north. Or Sami families came with their reindeer and started a new living. These events took place in many regions such as Setesdal, Hardangervidda, Hardanger, Voss, Hallingdal, Valdres, northern Gudbrandsdalen, Norefjell and Rendalen. In 1962 there were 20 000 tame reindeer held by 14 reindeer companies in southern Norway. Today five of these companies still exist. The reindeer owners have organized themselves as joint companies and to be a shareholder one must be living in the local municipality. The four companies in Valdres and northern Gudbrandsdalen keep in all about 11 000 reindeer in the winter herd which produces about 190 tons of reindeer meat each year. The legal basis of this reindeer management is regulated through agreements between the owners of the rough grazing properties and the company. In large areas the Norwegian State is the landowner, and in these cases the so-called Mountain law of 1975 regulates the agreement. The ways of managing the companies will be a matter of adjusting the management to all the other events in society. The structure of the herd, the extent of tameness and degree of domestication are key requisites. It is also of major importance that society supports this kind of management and regards the traditions and the long history of local interests in reindeer management. A future challenge will be to get these ways of living secured and warranted by law.